Periapical cemento-osseous dysplasia: A journey from diagnostic dilemma to accurate diagnosis with use of 3D imaging - Priyanka Tidke; Neha Gupta; Dipooja Patil; Mahesh Ghadage; Anamika Sinha; Pranita Dalave; Ramanpal S Makkad (Wolters Kluwer Medknow Publications, 2024)
Cemento-osseous dysplasia is a subgroup of fibro-osseous dysplasia commonly invading the tooth-bearing regions of the mandible quite often. These bony pathologies are asymptomatic and are seen on radiographs as an incidental finding. Accurate diagnosis of periapical cemento-osseous dysplasia is very crucial as it will help in the proper management of the patient as the incorrect diagnosis can lead to the unnecessary endodontic treatment of the concerned teeth as it may be misdiagnosed as a periapical pathology. We describe a case of periapical cemento-osseous dysplasia in which a 52-year-old woman had been experiencing discomfort in the right mental area of her mandible for the previous 6 months and had finally sought help at the outpatient department. This case study aims to highlight the significance of making an accurate diagnosis of cemento-osseous dysplasias in the tooth-bearing area.